2020
DOI: 10.3389/fvets.2020.00128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Stress on Measures of Anxiety and Fearfulness in Different Strains of Laying Hens

Abstract: Maternal stress can affect the offspring of birds, possibly due to hormone deposition in the egg. Additionally, phenotypic diversity resulting from domestication and selection for productivity has created a variety of poultry lines that may cope with stress differently. In this study, we investigated the effects of maternal stress on the behavior of different strains of laying hens and the role of corticosterone as its mediator. For this, fertilized eggs of five genetic lines-two brown (Brown 1 and 2), two whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 94 publications
(111 reference statements)
11
30
0
Order By: Relevance
“…The physical restraint procedure is a well validated test (39) that was used twice in this study: as a stressor in the parent stock and as a measure of stress response in the offspring. As previously reported (11), the layers from the MS treatment were still physiologically responsive to the stressor even after repeated exposure, therefore, validating the physical restraint test as a stressor in the MS treatment. However, no further stressors applied onto the breeder flock in the MS treatment were validated, thus limiting the discussion on whether the lack of effects in the progeny of MS breeders is due to a natural resilience of the breeder hens to the chosen stressors, or to an embryonic resilience to increased hormone levels deposited into the egg by the stressed breeder.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The physical restraint procedure is a well validated test (39) that was used twice in this study: as a stressor in the parent stock and as a measure of stress response in the offspring. As previously reported (11), the layers from the MS treatment were still physiologically responsive to the stressor even after repeated exposure, therefore, validating the physical restraint test as a stressor in the MS treatment. However, no further stressors applied onto the breeder flock in the MS treatment were validated, thus limiting the discussion on whether the lack of effects in the progeny of MS breeders is due to a natural resilience of the breeder hens to the chosen stressors, or to an embryonic resilience to increased hormone levels deposited into the egg by the stressed breeder.…”
Section: Discussionsupporting
confidence: 84%
“…Maternal stress can impact offspring’s physiology, behaviour and cognition (6,8) through structural and functional changes in brain areas involved in the mediation of fear and anxiety (9), as well as through changes in gene expression (10). We have previously shown that chicks from a commercial line of layer breeders that were subjected to daily sessions of psychological stressors during egg production showed a decreased occurrence of anxiety-like behaviour (measured in the total number of distress calls expressed during social isolation) compared to a control group (11). In addition, laying hens subjected to unpredictable feed restriction had chicks that stayed longer in tonic immobility (a measure of fearfulness) and spent less time eating when competing with birds from the control group for access to feed in a novel environment (12).…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al [82] reported that hens kept in colony cages had higher plasma CORT with greater fearfulness and feather damage compared to hens housed in colony cages with nest boxes. In contrast, Peixoto et al [83] reported that the effect of maternal stress on fearfulness in laying hens is not directly mediated by CORT. Similarly, in the current study, plasma CORT concentrations were not affected by the dietary treatment, regardless of its concentrations: 2.37 ng/mL (G-C), 2.19 ng/mL (G-0.5), 2.24 ng/mL (G-1.0).…”
Section: Discussionmentioning
confidence: 90%
“…Likewise, Japanese quails subjected to stressful events, such as sudden movement or unpredictable noise, laid eggs with higher yolk testosterone and progesterone, and produced chicks more sensitive to social separation (i.e., vocalized more during emergence and open-eld tests) 13 . Interestingly, stressful events applied onto ve genetic lines of layer breeders decreased offspring's sensitivity to social isolation in only one line, suggesting that maternal effects are also dependent on genetics 14 .…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no research has yet investigated the combination of maternal age and maternal environment in laying hens. The current study -which is part of a more comprehensive research project on maternal effects 14,26,[29][30][31][32] -investigates how maternal age, maternal rearing experience and maternal adult housing system affect their offspring's behaviour and stress response. For this, we conducted two experiments.…”
Section: Introductionmentioning
confidence: 99%